Implementasi Tata Tertib Sekolah dalam Membentuk Perilaku Belajar Siswa SMA Walisongo Gempol - Mardiyah, Mardiyah; Ismail, Moh.; Hidayat, Nanang; Zaini, Zaini; Widodo, Slamet (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
School rules are the provisions that govern daily school life. The obligation to obey school rules is important, obeying or obedience also has its own value, this value is a standard of behavior, a measure that determines one's behavior about good and bad, beautiful and not beautiful, obedient and disobedient, worthy and not worthy and so on. etc. These rules are part of the school system and not just as a school complement. The purpose of this study is to explain how the implementation of school rules in shaping student behavior. The type of research used in this study is a type of field research with a qualitative descriptive approach and to check the validity of the data using triangulation techniques. The results showed that First, the behavior developed in SMA Walisongo Gempol was student learning behavior in attending daily lessons, student learning behavior in reading books, student learning behavior in taking exams and the last one being student learning behavior in visiting the library. Meanwhile, the implementation of school rules in shaping student learning behavior at SMA Walisongo Gempol is a dress code and an order against prohibitions. Supporting factors in the implementation of school rules in shaping student learning behavior at SMA Walisongo Gempol, namely: a. The supporting factors are: school leadership, teachers, and students factors, community leaders factors. While the inhibiting factors areyourself and the environment.